Interprofessional Management of Chronic Orofacial Pain: A Topic Review, Steps to Improve Collaborative Care, and a Case Example - Kelly M. Wawrzyniak; Naila Ahmed; Ronald J. Kulich; Shuchi Dhadwal (Journal of the California Dental Association, 2024)
Background Orofacial pain is a specialty of dentistry that often encounters complex symptoms beyond the scope of dental practice, indicating a role for interprofessional teams in treating chronic orofacial pain.Discussion Interprofessional teams often include specialists from neurology, physical therapy, sleep medicine, and behavioral medicine, among others. Interprofessional practices can be difficult to achieve and require a commitment of communication, collaboration, co-location, and organizational support. A complex chronic orofacial pain case exemplifies the challenges for patients receiving sequential or siloed care, including delays in diagnosis, invasive procedures, and worsened disability. Common barriers to collaborative care and possible steps to close these gaps are discussed..